2018
DOI: 10.1016/j.heliyon.2018.e00582
|View full text |Cite
|
Sign up to set email alerts
|

Data gathering ability contributes to visual organization and probabilistic reasoning

Abstract: Individuals use data gathering methods to inform judgments and behaviors. Effective interaction with the environment depends on these having high accuracy and low noise, but when they become abnormal, aberrant thoughts and perceptions can occur. In this study, we examined if data gathering methods were consistent across tasks that relied on different cognitive abilities, specifically visual perception and probabilistic reasoning. Thirty-four non-clinical participants engaged in the Ebbinghaus Illusion and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 89 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…In turn, Wagner-Egger et al (2018) found the relationship between CBs and teleological thinking. The endorsement of conspiracy theories was also positively connected with cognitive biases: jumping to conclusion bias ( Pytlik et al, 2020 ; Kuhn et al, 2021 ; Sanchez and Dunning, 2021 ), liberal acceptance bias, bias against disconfirmatory evidence ( Georgiou et al, 2021b ; Kuhn et al, 2021 ), possibility of being mistaken ( Kuhn et al, 2021 ), and negatively associated with data gathering ability ( Bernadyn and Feigenson, 2018 ) and evidence integration ( Georgiou et al, 2021b ). People with high and low conspiracy mentality had different reactions to cues of epistemic authoritativeness ( Imhoff et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…In turn, Wagner-Egger et al (2018) found the relationship between CBs and teleological thinking. The endorsement of conspiracy theories was also positively connected with cognitive biases: jumping to conclusion bias ( Pytlik et al, 2020 ; Kuhn et al, 2021 ; Sanchez and Dunning, 2021 ), liberal acceptance bias, bias against disconfirmatory evidence ( Georgiou et al, 2021b ; Kuhn et al, 2021 ), possibility of being mistaken ( Kuhn et al, 2021 ), and negatively associated with data gathering ability ( Bernadyn and Feigenson, 2018 ) and evidence integration ( Georgiou et al, 2021b ). People with high and low conspiracy mentality had different reactions to cues of epistemic authoritativeness ( Imhoff et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%